2022
DOI: 10.3390/pathogens11020258
|View full text |Cite
|
Sign up to set email alerts
|

Nematode Orthologs of Macrophage Migration Inhibitory Factor (MIF) as Modulators of the Host Immune Response and Potential Therapeutic Targets

Abstract: One of the adaptations of nematodes, which allows long-term survival in the host, is the production of proteins with immunomodulatory properties. The parasites secrete numerous homologs of human immune mediators, such as macrophage migration inhibitory factor (MIF), which is a substantial regulator of the inflammatory immune response. Homologs of mammalian MIF have been recognized in many species of nematode parasites, but their role has not been fully understood. The application of molecular biology and genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…Various cell types, including immune‐, epithelial‐, endothelial‐, as well as smooth muscle cells, express MIF. MIF can inhibit the immunosuppressive effects of glucocorticoids and MIF induces pro‐inflammatory cytokines 6 . However, MIF does not appear to polarize the immune system into a specific direction, as it has been repeatedly shown to drive both type 1 and type 2 immune responses.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Various cell types, including immune‐, epithelial‐, endothelial‐, as well as smooth muscle cells, express MIF. MIF can inhibit the immunosuppressive effects of glucocorticoids and MIF induces pro‐inflammatory cytokines 6 . However, MIF does not appear to polarize the immune system into a specific direction, as it has been repeatedly shown to drive both type 1 and type 2 immune responses.…”
Section: Figurementioning
confidence: 99%
“…MIF can inhibit the immunosuppressive effects of glucocorticoids and MIF induces proinflammatory cytokines. 6 However, MIF does not appear to polarize the immune system into a specific direction, as it has been repeatedly shown to drive both type 1 and type 2 immune responses. In interferonc/tumour necrosis factor-driven type 1 immunity to bacterial infections MIFdeficient mice have trouble clearing bacteria but are protected from lipopolysaccharide or endotoxininduced sepsis.…”
mentioning
confidence: 99%
“…Indeed, macrophages can express markers such as CD206, CD200R and CD163 [ 25 ]. Treatment with migration inhibitory factor proteins (found on the filarial parasites W. bancrofti and B. malayi ) elicited M2-associated markers on murine macrophages in vitro, but in vivo alternative activation was also demonstrated in various helminth models [ 26 , 27 , 28 , 29 , 30 ]. With regard to ILC2 expansion in individuals infected with helminths, research on Schistosoma haematobium infection found lower frequencies of these cells in the peripheral blood of the egg-positive infants when compared to the egg-negative group [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophage migration inhibitory factor (MIF), a classical inflammatory cytokine [7][8][9][10][11][12][13][14], is also recognized as an adipokine [9,15,16]. Obese individuals often display higher plasma MIF levels compared to their lean counterparts [15,[17][18][19][20][21], suggesting a strong correlation between MIF and obesity.…”
Section: Introductionmentioning
confidence: 99%